KAJIAN PENGARUH PRA PENDINGINAN DAN SUHU PENYIMPANAN TERHADAP UMUR SIMPAN BROKOLI - Nur A. Blongkod; Frans Wenur; Ireine A. Longdong (COCOS, 2016)
ABSTRACTA study on the effect of pre-cooling and storage temperature to the storage life of Broccoli has been done. The objective of the study was to determine the changes in weight, changes in texture and color as well as changes in vitamin C of broccoli during storage and to obtain the pre-cooling methods and proper storage temperature which could extending the storage life of Broccoli. This research uses experimental method with descriptive analysis to explain the change in weight, color, vitamin C and texture that occurs in broccoli during storage. Several Broccoli were stored using a combination of treatments as follows: Treatment of pre-cooling (A) consists of: A0 - without pre-cooling, A1 - pre-cooling using water (23ºC), A2 - pre-cooling using ice water (0 °C) and tretment of storage temperature (B) consisting of: B0 - storage at room temperature (27ºC - 28ºC), B1 - storage at a temperature of 10ºC ± 2 °C, B2 – storage temperature of 5 °C ± 2 °C, and B3 - storage temperature of 0°C ± 2 °C. The results showed that broccoli with pre-cooling treatment using ice water at a temperature of 0 °C ± 2 °C is best. The broccoli has not changed in weight, the value of brightness was 40.74, still keep green color and the vitamin C content of 4.605 mg. with the value of hardness at the top of 0.09 mm/g and at the bottom of 0.08 mm/g. Broccoli stored with pre-cooling by ice water at a temperature of 0 °C ±2 °C has a longest storage life compared to other treatments, namely up to 42 days.Keywords: Broccoli, pre-cooling, storage temperature, shelf life